Paleozoic subduction of the southern Dunhuang Orogenic Belt, northwest China: metamorphism and geochronology of the Shuixiakou area. Issue 1 (1st January 2018) - Wang, Hao Y. C.; Zhang, Qian W. L.; Chen, Hong-Xu; Liu, Jia-Hui; Zhang, Hui C. G.; Pham, Van Tho; Peng, Tao; Wu, Chun‑Ming
Abstract: Amphibolites in the Shuixiakou area of the southern Dunhuang Orogenic Belt, southernmost Central Asian Orogenic Belt (CAOB), occur as lenses within hornblende-biotite-plagioclase gneiss or pelitic schist, exhibiting block-in-matrix feature of tectonic mélange. Three generations of metamorphic mineral assemblages (M1, M2, and M3) have been recognized in the garnet-bearing amphibolite lenses. The metamorphic prograde assemblage (M1) is documented with inclusion trails (hornblende + plagioclase + quartz) within garnet porphyroblasts, and are estimated to be formed under 610–690 °C and 6.5–10.2 kbar. The metamorphic peak assemblage (M2) consists of garnet + hornblende + clinopyroxene + plagioclase + quartz in the matrix and records metamorphic peak P - T conditions of 720–750 °C and 13.4–14.7 kbar. The retrograde assemblage (M3) is represented by the symplectic assemblage (hornblende + plagioclase + quartz ± biotite ± magnetite) rimming the garnet porphyroblast, formed in the decompression stage under P - T conditions of 630–730 °C and 3.8–7.2 kbar. The derived metamorphic P - T paths show similar tight clockwise loops including nearly isothermal decompression processes, typical of orogenic metamorphism. SIMS dating of metamorphic zircons from the amphibolites confirm that the high-pressure metamorphism (M2) occurred at ca. 438–398 Ma.